Treningsprosessen i distanseløp på internasjonalt nivå : En analyse av treningsmengde, treningsintensitet og krav til fysisk kapasitet - Tjelta, L. I. (2014)
Background: A limited number of studies have examined the distribution of training at different intensities during a training year among elite runners. It is well documented that the velocity at anaerobic threshold (vAT) correlates with level of performance in distance running. I have found no studies that have examined the correlation between vAT and the variables: maximal oxygen uptake (VO2max), utilization of maximum oxygen uptake (%VO2max) and running economy (RE) in elite runners. Purpose: The aim of this thesis is to answer the following main issues: 1: How did Norwegian junior and senior athletes who have reached the international level in distance running train? 2: What are the connections between running speed at the anaerobic threshold (vAT) and the variables maximal oxygen uptake (VO2max), running economy (RE) and the utilization of VO2max (% VO2max) in 34 middle- and long-distance runners who have been participants in different projects under the supervision of the Norwegian Athletic Federation? 3: What differences and similarities are there in the training of athletes featured in article I, II, III and IV, and how does their training match the training of elite distance runners reported in the research literature? 4: How do physiological test results of Norwegian elite runners match with the requirements the research literature sets for these test results for runners who perform at international level? Method: There has been done analyzes of the training diaries to: A) four male junior runners who were at European level in cross country running in 2008 (article I), B) six Norwegian long-distance runners at an international level (article II), C) Grete Waitz (GW) (article III) and D) Henrik Ingebrigtsen (HI) (article IV). The recorded training in the runners training diaries has been classified according to the intensities at which the training has been performed, and listed in different intensity zones. Tests of 34 elite runners (22 men and 12 women) were analyzed to describe the relationship between vAT and each of the three variables: VO2max, RE and %VO2max (Article V). Results: 1: Average weekly running volume for runners in this thesis is a stretched variable. Among the four junior runners mentioned in Article I, there was a variation in training volume from 110 to 180 km/week in the preparation period. Among senior runners the weekly running distance ranged from 121 km/week for GW to 216.8 km/week for runner E in Article II. All athletes have combined continuous running performed at low intensity with interval training and/or continuous running at an anaerobic threshold pace. The percentage of training in specific race pace increased in the pre competition period and during the competition season. 2: Among the 34 Norwegian runners, it was found that the three factors VO2max, RE and % VO2max explained 89% of the variation in vAT among the runners. For the group as a whole, VO2max was the only variable which was significantly correlated with vAT. Among men VO2max was also the only variable that was significantly correlated with vAT. Among women there was no correlation between vAT and any of the variables VO2max, RE and %VO2max. This is so remarkable that further studies should be related to the topic. 3: The four young distance runners referred to in Article I, ran more km/week than what has been reported for young Spanish runners and young Norwegian cross-country skiers. The senior runners mentioned in articles II, III and IV had training volumes in line with those previously reported in a limited number of scientific publications. 4: Runners discussed in this thesis have had VO2max values corresponding to the highest values reported in the research literature. The values for vAT and %VO2max reported in Article V are, due to different protocols, difficult to compare with other studies. It is recommended that in AT-tests in the future should be performed with 1% inclination on the treadmill instead of 1.7% as used today. Furthermore, it is recommended to work out a standard Norwegian test for estimating velocity at VO2maks (vVO2maks). Conclution: Runners who want to reach international level in distance running should run > 110 km/week at age of 18-19 years. For senior runners, it appears that training volumes around 150-200 km/week are to be recommended for 5000- and 10.000 m runners and 120-160 km/week for 1500 m runners. It also seems that combining such a weekly training volu me with 2-4 weekly sessions at anaerobic threshold pace and one weekly session with higher intensity is beneficial. In addition runners should do some sprint training and general strength training. It is also recommended to reduce the number of sessions at anaerobic threshold pace, and increase the number of sessions in specific race pace in the pre-competition period and during the competition season for those competing at distances from 1500 m to 10.000 m. Top results for the marathon can be reached by either a "low volume / high speed-model" (150-200 km/week) or a "high volume/ low speed-model" (180-260 km/week).